IMPLEMENTATION OF RAHN ACADEMIC IN SYARIAH PAWNTOWN - Shakila (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The development of sharia products is currently happening in Indonesia, especially in Islamic financial institutions, various kinds of products and contracts are applied in carrying out their business activities, one of the products is the rahn contract in sharia pawn shops. Basically, sharia-based products have special characteristics such as, not using interest in any form because it can cause usury, using money as a medium of exchange not as a traded commodity, and doing business to get rewards for the services performed. Although the pillars and conditions of the rahn contract have been carried out in accordance with sharia, there are still some things that must be clarified to get the correct practice in sharia theory. This study aims to find out how to apply rahn contracts to sharia pawnshops.